First report of Triatoma sordida Stal, 1859 (Hemiptera, Reduviidae, Triatominae) in the State of Acre and Brazilian Western Amazon - Ramos, Leandro Jose; Souza, Janis Lunier de; Souza, Claudio Rodrigues de; Oliveira, Jader de [UNESP]; Rosa, Joao Aristeu da [UNESP]; Aranha Camargo, Luis Marcelo; Cunha, Renildo Moura da; Oliveira Meneguetti, Dionatas Ulises de (Soc Brasileira Medicina Tropical, 2018)
Introduction: The occurrence of Triatoma sordida in the Brazilian Western Amazon is reported for the first time. Methods: Triatoma sordida specimens were collected from a Gallus gallus nest in a peridomiciliary area of Senador Guiomard municipality in the state of Acre. Results: The number of triatomine species in Acre increased from six to seven with this first report of T. sordida in the Brazilian Western Amazon. Conclusions: The occurrence of T. sordida in Acre is of concern since it is among the most captured triatomines in peridomiciliary environments in Brazil, and carries a high potential for vector transmission.
Keywords: Triatomines; Chagas disease; Trypanosomatids